Chapter Drone remote sensing for coastal habitats protection - Piccioli Resta, Giuseppe (Proceedings e report, 2020)
Growing beach tourist vocation of Lecce province has led to an increase human pressures along its coasts, often on habitats of conservation interest. Ever-increasing erosion phenomena of sandy shoreline constantly requires fast and effective monitoring activities assessing the conservation status of dunes and shoreline. Remote sensing via RPAS is proving useful to identify phenomena that act on a small scale and supporting and implementing protective measures with an adaptive management approach. This work consists of a protocol for monitoring dune cordons and nearby shorelines through RPAS.